2022
DOI: 10.1111/iep.12458
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term intake of aspartame‐induced cardiovascular toxicity is reflected in altered histochemical parameters, evokes oxidative stress, and trigger P53‐dependent apoptosis in a mouse model

Abstract: Aspartame (ASP) is probably the best known artificial sugar substitute that is used widely in food. Many experimental studies have reported the toxicity of long‐term administration of ASP in various organ tissues. However, there is little evidence available about the nature and mechanisms of the adverse effects of long‐term consumption of ASP on the cardiovascular system. This study was conducted to evaluate the possible effects of ASP on heart tissue. For this study 36 mature male mice were divided into one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Several in vivo and in vitro studies revealed altered scavenging mechanisms, increased lipid peroxydation, and enhanced generation of ROS/RNS in the erythrocytes or serum of aspartame-treated animals [ 20 , 98 , 99 ] or in human neuroblastoma cells [ 100 ]. The imbalance in ROS/RNS neutralization induced by aspartame can affect neutrophil adhesion, the phagocytic index, as well as antibody titers and soluble immune complexes in phagocytic and immune system cells, including neutrophils and lymphocytes [ 99 ].…”
Section: Mechanisms Of Toxicity Of Aspartame Metabolism Productsmentioning
confidence: 99%
“…Several in vivo and in vitro studies revealed altered scavenging mechanisms, increased lipid peroxydation, and enhanced generation of ROS/RNS in the erythrocytes or serum of aspartame-treated animals [ 20 , 98 , 99 ] or in human neuroblastoma cells [ 100 ]. The imbalance in ROS/RNS neutralization induced by aspartame can affect neutrophil adhesion, the phagocytic index, as well as antibody titers and soluble immune complexes in phagocytic and immune system cells, including neutrophils and lymphocytes [ 99 ].…”
Section: Mechanisms Of Toxicity Of Aspartame Metabolism Productsmentioning
confidence: 99%
“…Recent cohort studies also evidenced increased risk for cardiovascular diseases associated to high aspartame intake [15]. Several in vivo and in vitro studies have shown increased production of reactive oxygen/nitrogen species, lipid peroxydation and changes in scavenging systems in erythrocytes or serum of aspartame-treated animals [2,11,41] or in human neuroblastoma cells [21].…”
Section: Effect Of Aspartame On Cell Viability (By Pi Staining) Of Ch...mentioning
confidence: 99%